2023
DOI: 10.4236/ajcm.2023.131006
|View full text |Cite
|
Sign up to set email alerts
|

Application of Principal Component Analysis as Properties and Sensory Assessment Tool for Legume Milk Chocolates

Abstract: Principal component analysis (PCA) was employed to examine the effect of nutritional and bioactive compounds of legume milk chocolate as well as the sensory to document the extend of variations and their significance with plant sources. PCA identified eight significant principle components, that reduce the size of the variables into one principal component in physiochemical analysis interpreting 73.5% of the total variability with/and 78.6% of total variability explained in sensory evaluation. Score plot indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…These results are close to those from an earlier study assessing flavor and texture qualities in a dry yellow bean population that indicated an overall variation of 63% for three of its principal components (Bassett et al, 2021). Results from a study by Selvaraj et al (2023) on the sensory attributes of milk chocolates containing common bean and chickpea powder had a total of eight significant principal components and showed a higher variation of 78.6% in the tested data set. Results from another study by Oh et al (2022) had two significant principal components and recorded a variation of 89.6% of descriptive sensory data for different types of beans (black, kidney beans, mung beans, soybeans, red beans, and green kernel black beans) and chickpeas cultivated and consumed in TA B L E 5 Varimax rotated principal component factor loading for sensory attributes of selected common bean varieties.…”
Section: Principal Component Analysissupporting
confidence: 85%
See 4 more Smart Citations
“…These results are close to those from an earlier study assessing flavor and texture qualities in a dry yellow bean population that indicated an overall variation of 63% for three of its principal components (Bassett et al, 2021). Results from a study by Selvaraj et al (2023) on the sensory attributes of milk chocolates containing common bean and chickpea powder had a total of eight significant principal components and showed a higher variation of 78.6% in the tested data set. Results from another study by Oh et al (2022) had two significant principal components and recorded a variation of 89.6% of descriptive sensory data for different types of beans (black, kidney beans, mung beans, soybeans, red beans, and green kernel black beans) and chickpeas cultivated and consumed in TA B L E 5 Varimax rotated principal component factor loading for sensory attributes of selected common bean varieties.…”
Section: Principal Component Analysissupporting
confidence: 85%
“…PC1 was strongly correlated to stickiness, broken grains, juiciness, beany aroma, and chewability, thus primarily measuring the enhancement of sensory properties in the various common bean varieties (Table 5 ). In a different study assessing the sensory attributes of milk chocolate containing different levels of bean and chickpea powder, PC1 was positively correlated to appearance, texture, aroma, and mouthfeel (Selvaraj et al., 2023 ), an equivalence of broken grains classified under appearance, beany aroma and juiciness, stickiness, and chewability categorized under texture(mouthfeel) in this study. PC1 was also negatively correlated with astringency, metallic aroma, peeling of skin, particles, and hardness.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations